PENGARUH DEFISIT ANGGARAN PRIMER TERHADAP PRODUK DOMESTIK BRUTO, SUKU BUNGA, INFLASI DAN NERACA TRANSAKSI BERJALAN DALAM KERANGKA TEORI KONSENSUS BARU MAKROEKONOMIKA - , YB. Suhartoko, SE.,ME.; , Prof. Dr. Insukindro, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Objective of this study is to analyze the influence of the primary budget deficit to macro variables GDP, inflation and the current account. In addition, this study also analyzes the influence of the primary budget deficit to the monetary variable interest rates. The model built in this study based on the thought of New Macroeconomic Consensus and the Fiscal Theory of the Price Level, which is a combination of New Classical and New Keynesian theories. The theoretical framework used in this study is relatively new and different with other studies that analyze the effect of the primary budget deficit to the macro and monetary variables. I expect the result of this study to be useful to the academic world, the monetary authority and the fiscal authority. For the academic world, it, empirically, could contribute to the relatively new theoretical framework that can be developed in future studies. Moreover, it can provide a picture of economic conditions in Indonesia, in some theoritical framework debates of the influence budget deficit to national income, inflation and the current account. For policy makersâauthority, the results of this study could become an input, especially in terms of controlling inflation which the need to involve fiscal policy coordination between the monetary authoroty and the fiscal authority. In order to control inflation, policymakers need to pay attention to community rational expectations. The model built in this study consists of four equations, the good market equilibrium equation (IS), monetary policy equation (MP), inflation adjustment equation (IA) and the current account equations (CA). The model put forward elements of the IA equation . The equations are modified into error correction model Wickens and Breusch. The parameters in this model simultaneously estimated using the generalized method of moments. The test results showed an increase in short-term primary budget deficit will reduce GDP,while in the long run will increase GDP. The increase in the primary budget deficit will lead to higher interest rates in short term, whereas decrease interest rates in the long term.The increase in the primary budget deficit will decline inflation in the short term, whereas in the long term will lead to rising inflation.The increase in primary budget deficit will cause a decrease in the current account deficit in both the short and long term period.The increase of interest rates would lead to an increase of inflation, both in the short term and in the long term period.